The One who Dances Essentially Listens. (Revista Argentina de Musicología, 2018)
In this article I explore how tango dancers relate to music, and some intimacies of what happens in the milongas among the dancers and the music. Whoever dances, listens; and what he hears and how he hears it is the engine and sense of his dancing. His meeting in the embrace, his movements and tango steps are directly influenced by the uniqueness of each orchestra, and that identifies him. I like to think that every tango is a musical landscape to be explored in three minutes. The couples walk through on a constantly renewed way. In the milonga, the hearing and the moving are part of the same.
Keywords: tango; social dance; orchestras; dancers; musicality